2017
DOI: 10.1038/ncomms15182
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-alpha suppresses autophagy and induces neural tube defects via miR-129-2 in diabetic pregnancy

Abstract: Gene deletion-induced autophagy deficiency leads to neural tube defects (NTDs), similar to those in diabetic pregnancy. Here we report the key autophagy regulators modulated by diabetes in the murine developing neuroepithelium. Diabetes predominantly leads to exencephaly, induces neuroepithelial cell apoptosis and suppresses autophagy in the forebrain and midbrain of NTD embryos. Deleting the Prkca gene, which encodes PKCα, reverses diabetes-induced autophagy impairment, cellular organelle stress and apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 65 publications
2
90
0
Order By: Relevance
“…The transgene DN FoxO3a, along with a separate cell nucleus localized GFP, were driven by the Nestin promoter from E8.0 onward. 5 GFP localized in the nucleus confirmed neuroepithelium-specific expression of the transgenes (Figure 3, B). The NTD rate in DN FoxO3a embryos was significantly lower than in WTembryos under maternal diabetic conditions (Figure 2, C and D, and Table 2).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The transgene DN FoxO3a, along with a separate cell nucleus localized GFP, were driven by the Nestin promoter from E8.0 onward. 5 GFP localized in the nucleus confirmed neuroepithelium-specific expression of the transgenes (Figure 3, B). The NTD rate in DN FoxO3a embryos was significantly lower than in WTembryos under maternal diabetic conditions (Figure 2, C and D, and Table 2).…”
Section: Resultssupporting
confidence: 57%
“…5 Cellular organelle stress, including proapoptotic kinase activation, endoplasmic reticulum stress, and autophagy impairment, has been shown to occur in the developing neuroepithelium exposed to maternal diabetes. 5,1114 Autophagy, an intracellular catabolic process, removes dysfunctional protein aggregates and damaged cellular organelles, and thus maintains intracellular homeostasis. The autophagy process starts with the formation of double membrane vacuoles, called “autophagosomes,” which requires a group of proteins derived from autophagy-related genes (Atgs).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of NH 4 Cl, the ratio of LC3B II/I tended to increase in HG‐treated NSCs. However, a recent study reported that HG inhibited E10.5 brain autophagy in vivo . Our explanation for this discrepancy is as following: (a) we used NSCs mainly at E11.5 and (b) we examined the relationship between autophagy and HG in vitro and autophagic flux could be easily blocked, but autophagic flux was hardly blocked in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…The ApopTag Red In Situ Apoptosis Detection Kit (Millipore) was used to detect apoptotic cells as previously described(Wang et al , 2017). Briefly, formalin-fixed brain tissues were dehydrated by series of 50%–100% ethanol and then embedded in paraffin for sectioning.…”
Section: Methodsmentioning
confidence: 99%